Pengaruh Beban Kerja Terhadap Kinerja Pekerja Harian Lepas di PT Kreasi Indonesia Putra - Gautama, I Made Lingga; Citrawati, Luh Putu; Sumadi, I Gede (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
PT. Kreasi Indonesia Putra is an event organizer based in Bali, founded by Ihsan Halomoan Dili Lubis. Currently, PT. Kreasi Indonesia Putra has developed into a competent professional event organizer for both national and international events. The services provided by PT. Kreasi Indonesia Putra include activities such as production, gala dinners, meetings, conferences, team building, exhibitions, and incentive tours.This study aims to examine the influence of workload on the performance of freelance daily workers. The population consisted of all workers, with a sample of 38 freelance respondents. Data collection was conducted using questionnaires, analyzed through instrument testing, classical assumption tests, and multiple linear regression analysis. The results indicate that workload has a negative and significant effect on employee performance, based on a t-value of -6.108 and a significance level of 0.000. The magnitude of workload's influence on employee performance is 50.9%. Recommendations include assigning tasks according to available time and employee capabilities, providing regular training and guidance to employees, and supervising employees in carrying out their duties.